sidik jari DNA 30 genotipe padi (oryza sativa L) Berdasarkan marka SSR yang terpaut dengan kandungan Zn - Kinasih Sekar Pamungkas; Muharram Muharram; Rommy Andhika Laksono; Untung Susanto (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study to determine the PIC (polymorphic information content), gene diversity, and rice genotype groupings tested based on SSR markers reported to be associated with high Zn content traits in 30 genotypes. used the SSR Marking Application (Simple Sequence Repeats The research was carried out from May 2021 to September 2021 at the Center for Rice Research in Sukamandijaya Village, Ciasem District, Subang Regency, West Java Province. The study used descriptive analysis by observing the DNA banding pattern using 9 SSR primers. The results showed that 50 alleles were detected in 30 rice genotypes with an average number of marker alleles of 5.55 and a range of 3-10 alleles per locus, the average frequency of major alleles was 0.46 with the lowest value of 0.20 at the RM234 marker and the highest value of 0. 67 at the RM8226 mark. Heterozygosity values ranged from 0.0 at RM137 to 0.73 at the RM234 rice SSR marker with a mean of about 0.29. The value of diversity is between 0.50 (RM 8226) to 0.86 (RM 234, RM223) with an average of 0.67. The PIC (polymorphic information content I) value ranged from 0.44 (RM 152) to 0.85 (RM337) with an average of 0.62. Phylogenetic analysis showed that 3o rice genotypes were divided into 6 main groups with a coefficient of 0.45. The first cluster consists of 8 genotypes of rice, the second cluster has 1 genotype of rice, the third cluster has 13 genotypes of rice, the fourth cluster has 3 genotypes of rice, the fifth cluster has 1 genotype and the sixth cluster consists of 4 genotypes of rice.